Altered monocytic phenotypes are linked with systemic inflammation and may be linked to mortality in dialysis patients - Brandt, Sabine; Ewert, Lara; Scurt, Florian G.; Reichardt, Charlotte; Lindquist, Jonathan A.; Gorny, Xenia; Isermann, Berend; Mertens, Peter R. (Scientific reports, 2019)
The major causes for increased morbidity and mortality among chronic kidney disease patients are cardiovascular diseases and infection. A causal link between an activated immune system and aggravated atherosclerosis has been postulated that skews the system towards inflammatory responses. Previously, we demonstrated a positive association of pro-inflammatory cytokines with monocytic Y-box binding protein-1 (YB-1) expression and vessel wall infiltration in hemodialysis patients. Here, we question whether the responsiveness and cytokine repertoire of monocytes is altered by pre-activation and how this correlates with survival. EDTA whole blood from hemodialysis patients (n = 45) and healthy controls (n = 34) was collected and leukocytes challenged with LPS. The distribution of monocyte subsets, YB-1 acetyl content, and serum cytokine levels were determined. Compared to controls, dialysis patients have fewer classical (Mo1) and more intermediate (Mo2) and non-classical (Mo3) monocytes. In response to LPS, the Mo2 subset significantly increases (p < 0.001) in control subjects, but not in hemodialysis patients; increased CD86 expression indicates a positive response to LPS. Based on the changes within Mo2, subjects could be classified as responders or non-responders: 60% non-responders were seen in the dialysis cohort versus only 35% among healthy controls. YB-1 acetylation is higher in dialysis patients, independent of LPS stimulation. In this small cohort with 72 months follow-up period intracellular YB-1 acetyl levels, IL-6, uPAR, and IP10 correlated with excess mortality in the dialysis cohort. Changes in YB-1 acetylation and serum cytokines may, at a given time point, possibly predict the long-term outcome and thus provide a legacy effect in hemodialysis patients.